Sufi quietism between Al-Ghazzali's Islamic philosophy and the Jihad of Uthman ibn Fudi (2008)
This paper studies the Jives and teachings of two leading Sufi scholars, Imam Abu Hamid Muhammad Ibn Muhammad Al-Ghazzali (450/1058-505/1111) and Shaykh 'Uthman Ibn Fudi (1754-1817) in respect of the belief that Suli s generally live a quietist life. It focuses on the mass quietist appeal of the Sufi movement by studying Al-Ghazzali's recourse to Islamic Philosophy in his mystical interpretation and experience and the Sufi Da'wah and Jihad of 'Uthman Ibn Fudi in pre-colonial Nigeria. Against the above background of the Sufi doctrines of peaceful and quietist life, the paper shows how both the Sufi conceptions of Islamic philosophical mysticism and jihad sought to bring about an Islamic reformation both in space and time through a peaceful movement. The paper offers a justification for this Sufi quietist practice and demonstrates that while Sufis uphold the Islamic philosophical virtues of being at peace with all that is around them, they also do rise up in revolution by physically defending themselves when the need arises.